2014
DOI: 10.1504/ajesd.2014.065580
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and economic growth in Sub-Saharan Africa: a panel data analysis

Abstract: This article investigates the behavior of equilibrium exchange rate and real exchange rate misalignment in Sudan over the period 1979-2009. In addition, the impact of real exchange rate misalignment on economic performance is examined. The empirical results show that the equilibrium exchange rate is significantly influenced by economic policy variables such as trade openness, government expenditure and taxes. The results also reveal that the Sudanese economy has exhibited an exchange rate overvaluation over th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 14 publications
3
16
1
Order By: Relevance
“…The Classical Theory of Compensation by Marx (1961) argued in favour of a positive link between ICTs and employment, on the premise that technological innovation may create additional employment in the capital goods sector even after technologies have displaced workers. Also, the compensation mechanism may manifest through a decrease in prices resulting from a decrease in the cost of production and consequently creates new demand for product and employment (Ebaidalla, 2014; Vivarelli, 2007). In general, jobs lost due to new technologies may be compensated through the creation of opportunities for unemployed workers, driven by new products and investment that will create additional new jobs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…The Classical Theory of Compensation by Marx (1961) argued in favour of a positive link between ICTs and employment, on the premise that technological innovation may create additional employment in the capital goods sector even after technologies have displaced workers. Also, the compensation mechanism may manifest through a decrease in prices resulting from a decrease in the cost of production and consequently creates new demand for product and employment (Ebaidalla, 2014; Vivarelli, 2007). In general, jobs lost due to new technologies may be compensated through the creation of opportunities for unemployed workers, driven by new products and investment that will create additional new jobs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In any case, studies that have shown concern about the employment impact of ICTs across countries of the world have been inclusive. Several studies have reported in favour of positive effects of technological progress on employment generation (Ebaidalla, 2014; Meyer‐Krahmer, 1992; Simonetti et al, 2000; Sinclair, 1981; Whitley & Wilson, 1982), while few others have reported negative effects (Brouwer et al, 1993; Machin & Van Reenen, 1998; Zimmermann, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations